2018
DOI: 10.1159/000491926
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Genotype 3 Genomes from RNA-Positive but Serologically Negative Plasma Donors Have CUG as the Start Codon for ORF3

Abstract: Hepatitis E virus (HEV) is a pathogen that causes hepatitis worldwide. Molecular studies have identified HEV RNA in blood products although its significance is not understood. This study was undertaken to characterize HEV genomes in asymptomatic plasma donors from Sweden and Germany lacking anti-HEV. Complete open reading frames (ORFs) were obtained from HEV strains in 5 out of 18 plasma donors who tested positive for HEV RNA. All strains had CUG as the start codon of ORF3, while 147 GenBank strains all had AU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
(50 reference statements)
1
14
0
Order By: Relevance
“…Although the Spanish wild boars were older than the Swedish, they had similar incidence of HEV RNA, which may indicate that they have a higher frequency of chronic HEV infections. Several of these strains were found on the branch with 3c/i strains in the phylogenetic tree and were genetically similar to strains from human chronic carriers (Norder et al., ). Whether some strains may be more likely to cause chronic infection than other HEV strains also in animals need further investigation.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although the Spanish wild boars were older than the Swedish, they had similar incidence of HEV RNA, which may indicate that they have a higher frequency of chronic HEV infections. Several of these strains were found on the branch with 3c/i strains in the phylogenetic tree and were genetically similar to strains from human chronic carriers (Norder et al., ). Whether some strains may be more likely to cause chronic infection than other HEV strains also in animals need further investigation.…”
Section: Discussionmentioning
confidence: 91%
“…Similar non‐immunological response has been observed in humans, who may have detectable HEV RNA in serum for up to 59 days without detectable anti‐HEV (Westholter et al., ). Such strains have been shown to have a modified start codon for the ORF3 protein and may be immune escape variants (Norder et al., ). Little is known about the virulence of these strains which needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a novel and surprising finding, implying that HEV RNA analyses should be included when evaluating for possible HEV infections. Norder et al [17] have reported a hypothesis aiming at explaining why some patients do not seroconvert despite documented HEV exposure. They noted that HEV RNA positive, but serologically negative, plasma donors have a genomic HEV variant containing a CUG sequence instead of AUG as the start codon for open reading frame ORF3.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that HEV RNA positive, but serologically negative, plasma donors have a genomic HEV variant containing a CUG sequence instead of AUG as the start codon for open reading frame ORF3. The subsequent lower expression of the encoded ORF3 protein may alter its impact on innate immune responses as well as type I interferon production, resulting in lower seroconversion rates [17].…”
Section: Discussionmentioning
confidence: 99%